Simulation of light focusing by a dielectric microcylinder with a metal film and gap on shadow side. Issue 1 (February 2021) - Savelyeva, A A; Kozlova, E S
Abstract: In this work, using the FullWAVE software package, numerical simulation of focusing of TM-wave with a wavelength of 633 nm was performed. It is shown that a dielectric microcylinder made of polyester with a radius of 2.1749 of wavelength coated on the shadow side with a silver film of 90 nm with a 100 nm hole, allows to get a focus with a maximum intensity of 1.37 times more (10.61 a. u), than a conventional dielectric cylinder (7.73 a. u).